If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8x + 7 = 4x + 47 Reorder the terms: 7 + 8x = 4x + 47 Reorder the terms: 7 + 8x = 47 + 4x Solving 7 + 8x = 47 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. 7 + 8x + -4x = 47 + 4x + -4x Combine like terms: 8x + -4x = 4x 7 + 4x = 47 + 4x + -4x Combine like terms: 4x + -4x = 0 7 + 4x = 47 + 0 7 + 4x = 47 Add '-7' to each side of the equation. 7 + -7 + 4x = 47 + -7 Combine like terms: 7 + -7 = 0 0 + 4x = 47 + -7 4x = 47 + -7 Combine like terms: 47 + -7 = 40 4x = 40 Divide each side by '4'. x = 10 Simplifying x = 10
| x+10-18=-5 | | 45+35x=20+40x | | y=2mx+7b | | 2(3x+1)-3(-4x+1)=20x-19 | | X+17=12-19 | | 4x^2+5=2y | | -16=x+(-22) | | 4n-5=-17 | | -8(5n+7)=40-8n | | 4x-6+42=90 | | 2[d-(4d+13)+3]=2(d+10) | | 22.5x-15.0=12 | | 2y(6z-x)= | | 48+x=4 | | -5y-5(5z-3y)+3= | | 10p=170 | | 5-(2x+5)=-7 | | 18=0.5 | | -15.5n+17.23+5n=-12.8n-11.06 | | [t+6]=4 | | 3(x+4)-5(2x+3)=-6(x-2)+2(x-6) | | 5-2n=67 | | 64-x=42 | | y-(-6)=2 | | 13x+5x=10 | | 5=17(4x+28) | | 5y=15y+60 | | -13.1+18w=18.2w-10.86 | | 2ab-5ab= | | 1341-4.5x=x | | -11+y=27 | | 2x+12=2x-48 |